Test of Flat Burr Mill Type Grinder In Red Rice Commodity - Margaretta Bukit; Saipul Bahri Daulay; Adian Rindang (Universitas Sumatera Utara, 2014)
One of the components which determines the post-harvest handling technology is the use of post-harvest equipment, such as a flat burr mill type bean grinder. This study was aimed at examining the coffee bean grinder flat burr mill type using red rice with three level of smoothness, i. e: level 1, level 2 and level 3. Parameters observed were: equipment effective capacity, percentage of lose material, smoothness of milled red rice and carbohydrate content.The results showed that the effective capacity at smoothness 1 was 8.13 kg/h, smoothness 2 was 13.88 kg/h and smoothness 3 was 18.558 kg/h. percentage of material lost at smoothness 1 was 1.034 %, at level 2 was 0.234 % and level 3 was 0.151 %. The size of red rice milled for all level was 50 mesh. The carbohydrate content of red rice at level 1 was 79.4975 % , at level 2 was 78.5546 % and at level 3 was 78.0174 % . Keywords : flat burr mill , red rice , test of equipment, milled red rice.